Disturbance of gut microbiota in diabetes related macroangiopathy: Evidence from the gut bacteriome and mycobiome - Xiaoling Gou; Yuqing Chen; Yi Zong; Xuemei Huang; Yihong Shen; Lijie Wang; Yifan Liu; Yuchi He; Jialong Jia; Xiyu Zhang; Sihan Peng; Xianhua Zhou; et al. (iScience, 2025)
Summary: Diabetes related macroangiopathy (DMA) is a major complication of type 2 diabetes (T2D), impacting both morbidity and mortality. This study characterized the gut bacteriome and mycobiome in 179 adults, including 58 with DMA, 71 with T2D, and 50 healthy controls. The gut microbiome of DMA subjects exhibited reduced alpha diversity, and a distinct microbial composition compared with healthy control. Two bacterial families, six bacterial genera, and four bacterial species exhibited significant differences between DMA and T2D subjects. Additionally, in the mycobiome group, Xylariales was significantly decreased in DMA subjects compared with T2D subjects. Disruptions in transkingdom interactions between gut bacteria and fungi supported microbiota dysbiosis in DMA. A diagnostic model combining bacterial and fungal markers achieved an AUC of 94.20%. This work deepens our understanding of the microbial landscape associated with macroangiopathy in diabetes and highlights potential microbial targets for diagnostics and therapeutic intervention.